Are Character Traits Dispositions?. (16th May 2017) - Alvarez, Maria
Abstract: The last three decades have seen much important work on powers and dispositions: what they are and how they are related to the phenomena that constitute their manifestation. These debates have tended to focus on 'paradigmatic' dispositions, i.e. physical dispositions such as conductivity, elasticity, radioactivity, etc. It is often assumed, implicitly or explicitly, that the conclusions of these debates concerning physical dispositions can be extended to psychological dispositions, such as beliefs, desires or character traits. In this paper I identify some central features of paradigmatic dispositions that concern their manifestation, stimulus conditions, and causal bases. I then focus on a specific kind of psychological disposition, namely character traits, and argue that they are importantly different from paradigmatic dispositions in relation to these features. I conclude that this difference should lead us to re-examine our assumption that character traits are dispositions and, by implication, whether we can generalize conclusions about physical dispositions to psychological dispositions, such as character traits and their manifestations.